Complexity to compatibility: Sino-Indian bilateralism concerning maritime security. (3rd July 2019) - Yadav, Dhanwati
ABSTRACT: In global politics, the relations between India and China have long been branded by the countries' customary rivalry. Bitterness and resentment between the two came to the fore with the exile of Dalai Lama to India in 1959. Subsequent to this episode, the Sino-Indian war of 1962 further exacerbated their already strained ties. The continued border dispute, much importantly added fuel to fire. Altercations in their relations, thus are yet not extinguished. In the twenty-first century, when these Asian giants are putting forward their soft power together with military muscle through economic persuasion, the waters of the Indian Ocean are sponsoring economic and geo-strategic conflicts between the two. "India's participation in the new alliance formed in the maritime domain whereas could cause increasing insecurities to Beijing, Beijing's unregulated assertiveness through monetary aids along with modernized naval tactics is also viewed to have escalated India's security concerns". The global powers when examine such bilateral equation with probabilities of drawing complexities, cooperation between the two, in the form of an unprecedented "maritime dialogue", demonstrate their unabated commitment to ensure maritime security while pursuing their geo-strategic ambitions in the region. Developments of this kind can help promote regional peace as well.